Improvement in the outcome of invasive fusariosis in the last decade. (18th November 2013) - Nucci, M.; Marr, K. A.; Vehreschild, M. J. G. T.; de Souza, C. A.; Velasco, E.; Cappellano, P.; Carlesse, F.; Queiroz‐Telles, F.; Sheppard, D. C.; Kindo, A.; Cesaro, S.; Hamerschlak, N.; et al.
Abstract Invasive fusariosis (IF) has been associated with a poor prognosis. Although recent series have reported improved outcomes, the definition of optimal treatments remains controversial. The objective of this study was to evaluate changes in the outcome of IF. We retrospectively analysed 233 cases of IF from 11 countries, comparing demographics, clinical findings, treatment and outcome in two periods: 1985–2000 (period 1) and 2001–2011 (period 2). Most patients (92%) had haematological disease. Primary treatment with deoxycholate amphotericin B was more frequent in period 1 (63% vs. 30%, p <0.001), whereas voriconazole (32% vs. 2%, p <0.001) and combination therapies (18% vs. 1%, p <0.001) were more frequent in period 2. The 90‐day probabilities of survival in periods 1 and 2 were 22% and 43%, respectively (p <0.001). In period 2, the 90‐day probabilities of survival were 60% with voriconazole, 53% with a lipid formulation of amphotericin B, and 28% with deoxycholate amphotericin B (p 0.04). Variables associated with poor prognosis (death 90 days after the diagnosis of fusariosis) by multivariable analysis were: receipt of corticosteroids (hazard ratio (HR) 2.11, 95% CI 1.18–3.76, p 0.01), neutropenia at end of treatment (HR 2.70, 95% CI 1.57–4.65, p <0.001), and receipt of deoxycholate amphotericin B (HR 1.83, 95% CI 1.06–3.16, p 0.03). Treatment practices have changed over the last decade, with an increased use of voriconazole and combination therapies. There has been a 21% increase in survival rate in the last decade.